Optimization of the Implementation of Psychosocial Assistance of Sexual Crimes During the COVID-19 - Siti Fatmawati; Rifkah Anniza Rahman; Sri Khayati (Indonesian Journal of Multidisciplinary Science, 2023)
This study aims to determine the process of implementing psychosocial assistance to child victims of sexual crimes in Kendari City and to find out what obstacles are faced by implementing psychosocial assistance to child victims of sexual crimes. This research was conducted in Kendari City, the Integrated Service Center for Women and Children Empowerment, hereinafter abbreviated as P2TP2A, and the Kendari City Social Service. This writing is done by conducting field studies by conducting interviews as well as obtaining documents related to the problems in the author's writing by using Qualitative methode. This Research aims to reduce the case problem of sexual crimes. Interviews were conducted by asking questions that were relevant to the topic posed. The second approach is to describe descriptively various interview results and then analyze the data. The process of handling victims in this case the implementation of psychosocial assistance is carried out only as an examination process only to complete the examination file at the police. If the police receive a complaint report, the police will contact P2TP2A and the Social Service to seek psychosocial assistance for children who are victims of sexual crimes. On the other hand, if P2TP2A or the Social Service have received reports of sexual crimes against children, P2TP2A and the Social Service will coordinate with the Police so that perpetrators of these sexual crimes can be prosecuted.